Muscle synergy during Wingate anaerobic rowing test of collegiate rowers and untrained subjects - Shaharudin, S.; Zanotto, D.; Agrawal, S. (International Journal of Sports Science, 2014)
The purpose of this study was to evaluate the muscle synergies during Wingate anaerobic rowing test of collegiate rowers and physically active individuals who were not specifically trained in rowing. As a power-endurance sport, high anaerobic capacity is one of the determinants of rowing performance. Due to the close link that exists between the state of energy supply and types of muscle fibers being recruited, the relationship of muscle synergies and rowing economy during an anaerobic dominant activity was investigated. Method: Ten subjects were recruited for both groups. Muscle synergies were extracted from 16 rowing specific muscles using Principal Component Analysis (PCA) with varimax rotation. An all out Wingate anaerobic rowing test was performed on Concept 2 sliding ergometer. Rowing performance, muscle synergies and physiological variables were analyzed. Results: Rowers showed better rowing performance in terms of peak power output, mean power output, distance covered, maximal oxygen consumption and energy expenditure compared to the untrained subjects. Three muscle synergies were extracted from both groups with some variability of timing coefficients and muscle weightings. A significant association was found between Synergy #1 and rowing economy, although there was no difference among the groups. Discussion: Expertise in rowing was related to the ability to adjust the sequence of synergies activation and the muscle weightings activation level during intense anaerobic burst. The rowers could apply the results from this study to improve rowing economy especially during the start of the rowing race, where anaerobic metabolism is predominant.